2006
DOI: 10.1111/j.1365-2036.2006.02885.x
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged n‐3 polyunsaturated fatty acid supplementation ameliorates hepatic steatosis in patients with non‐alcoholic fatty liver disease: a pilot study

Abstract: SUMMARY BackgroundRecent studies suggest a role of n-3 long-chain polyunsaturated fatty acids (n-3 PUFA) as peroxisome proliferator-activated receptor-a ligands in improving non-alcoholic fatty liver disease (NAFLD) in rodents. However, data in humans are still lacking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
258
2
12

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 377 publications
(291 citation statements)
references
References 43 publications
12
258
2
12
Order By: Relevance
“…139 Omega-3 fatty acids, currently approved in the United States to treat hypertriglyceridemia, have been investigated to treat NAFLD both in animal models and in humans. 141 A recent review by Masterton et al, 142 of published literature related to omega-3 fatty acids in NAFLD, found experimental evidence to support their use but the interpretation of human studies was limited by small sample size and methodological flaws. A large multicenter study of one omega-3 fatty acid (eicosapentanoic acid) to treat NASH is ongoing in the United States.. More than a dozen other miscellaneous agents have been investigated in small, proof-of-concept studies and their detailed evaluation is beyond the scope of this guideline.…”
Section: Vitamin Ementioning
confidence: 99%
“…139 Omega-3 fatty acids, currently approved in the United States to treat hypertriglyceridemia, have been investigated to treat NAFLD both in animal models and in humans. 141 A recent review by Masterton et al, 142 of published literature related to omega-3 fatty acids in NAFLD, found experimental evidence to support their use but the interpretation of human studies was limited by small sample size and methodological flaws. A large multicenter study of one omega-3 fatty acid (eicosapentanoic acid) to treat NASH is ongoing in the United States.. More than a dozen other miscellaneous agents have been investigated in small, proof-of-concept studies and their detailed evaluation is beyond the scope of this guideline.…”
Section: Vitamin Ementioning
confidence: 99%
“…4 This effect is attributable mainly to the combined effects of inhibition of lipogenesis and stimulation of fatty acid oxidation in the liver. 5,6 Fish oil supplementation may be effective in the prevention of NAFLD; however, it is not clear whether fish oil is effective against all types of fatty liver.…”
mentioning
confidence: 99%
“…More importantly, most of the studies did not evaluate histological endpoints of treatment. Among the first trials, Capanni et al found that PUFA improved liver aminotransaminases, metabolic profiles and hepatic steatosis on imaging [54]. Other studies have provided collaborative observations [53].…”
Section: Thiazolidinedionesmentioning
confidence: 98%